Perspectives on the tensions in teaching with technology in Norwegian teacher education analysed using Argyris and Schön’s theory of action - Thorvaldsen, Steinar; Madsen, Siri Sollied (Education and Information Technologies, 2020)
Teachers’ professional digital competence (PDC) is of increasing importance in classrooms in the majority of EU countries. Norway is one of the countries that has been exposed to a strong top-down implementation of information and communication technology in education. However, despite national efforts, practitioners in the education system do not seem to work in line with the given policy. There is therefore a gap between the micro and macro levels, necessitating the need for a closer exploration of the issue. We have conducted a quantitative study of teacher educators and their students in Northern Norway ( N = 112). Amongst the staff, professional attitudes have a stronger impact than PDC regarding the extent of the educational use of digital tools, whereas amongst students, PDC has a stronger influence. These results are interpreted using Argyris and Schön’s theory of action in learning organisations.